Prevalence And Risk Factors Of Job Strain Among Laboratory Technicians In Hospital Universiti Sains Malaysia. - Aziah, B.D.; Rusli, B.N.; T Winn, Dr PH; Tengku, M.A.; Nain, L (2004)
Several sources of job stress exist. Some of these stressors are intrinsic to the job,while some are related to psychosocial and other factors.